A Design Thinking Approach for Entrepreneurship Education - Sethi, Ritika; Sachdeva, Rajat (Journal of Advanced Research in English & Education, 2021)
Entrepreneurship has traditionally been taught from a business administration perspective, where predicting the future is central and where the world is seen as linear with known inputs and outputs. The world of entrepreneurs is a quite different, usually highly uncertain environment, and therefore requires a different type of skill set. In this paper, we conceptualize entrepreneurial learning through a method- and design-based approach and illustrate how a course can be developed and designed. In this paper it is argued that by utilizing design thinking and a methods approach, learning from a “through” approach can be achieved. This learning is more focused on the entrepreneurial process, highlighting the role of skills and mindset. This learning approach enables student-centered learning and focus on skills more applicable to entrepreneurs. It is also argued that the entrepreneurship process is not linear; therefore, creativity is central and finding structure is an unstructured process. Design thinking emphasizes a practical approach where students step outside the classroom. This experimentation and interaction in the real world of users and customers with real feedback is important in combination with reflection exercises. How to cite this article: Sethi R, Sachdeva R. A Design Thinking Approach for Entrepreneurship Education. J Adv Res Eng & Edu 2020; 5(4): 1-7.